STATISTICAL ANALYSIS AND COMPARISON OF DATA ON PATIENTS WITH THYROID CANCER IN THE REPUBLIC OF NORTH MACEDONIA AND THE REPUBLIC OF CROATIA IN THE PERIOD FROM 2014 TO 2018 - Arsovska, Blagica; Zhu, Jihe; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2020)
Thyroid cancers have been on the rise in recent years. One of the direct causes is the increase in ionizing radiation. The incidence is three times higher in women than in men. Most of the patients are over 50 years old. There is also a genetic predisposition. The aim of the paper is to differentiate between the results obtained for patients with thyroid cancer in Republic of North Macedonia and Republic of Croatia and to see if this type of cancer is on the rise in both countries and if the numbers are approximate in a period of 6 years from 2013 to 2018. The total number of newly diagnosed cases of malignant neoplasm of the thyroid gland in R.N. Macedonia in the period from 2014 to 2017 is 315, while in the Republic of Croatia in the same period the number of newly discovered cases is 8 times higher than in RN Macedonia and has a total of 2796 newly diagnosed patients. In RN Macedonia the incidence or the number of new patients with thyroid cancer for both sexes is increasing. The increased incidence is probably due to the increased increase in diagnosis of the disease in the early, subclinical stages (small papillary carcinoma). Survival from thyroid cancer depends on the stage at which it is detected, generally the percentage of survivors is high. Due to the possibility of recurrence, regular check-ups are required.